The association of gender diversity in the compensation committee and CEO remuneration: evidence form UK - YU, SIMIN (2019)
Abstract Executive compensation has been a hot issue for investors, policymakers and scholars. The global trend of enhancing female representation on board also drives the study related to gender diversity and corporate governance effectiveness. This paper aims to investigate that whether the gender diversity of the compensation committee is negative associated with the CEO pay setting, and whether the presence of female directors in the committee could improve the link between the CEO remuneration and firm performance. Based on the result of panel regression method and the sample collected from FTSE 350 public companies in the London Stock Exchange during 2012 to 2018 financial year period, the results suggest that the integration of female directors in the sub of boardroom may have little impact on CEO pay package, and gender diversity of compensation committee does not significantly improve the pay-performance link.